European wonders at the court of Siam - Sarah Benson (2018)
With this fragment of dialogue begins the likewise fragmentary journal of Ok- Phra Wisut Sunthon, known more familiarly as Kosa Pan, Siamese ambassador to France in 1686-87.1 The next event in his narration, "Those ladies then departed," allows us to reconstruct the scene. Kosa Pan is aboard the Oiseau, the ship that has brought him and two coadjutants from Siam on a diplomatic mission to the court of Louis XIV. There he has been the object of curiosity for the first French women to get a look at him after his arrival in their country, and he has assured them that he is just as curious about them. Kosa Pan's polite address to the women of France introduces a period in the late seventeenth century of keen mutual interest between the Europeans and Siamese. Thanks to Kosa Pan's lengthy stay in France, there was an enormous curiosity in Europe about Siam and the Siamese. While the ambassadors themselves were paying visits to the great homes of France, touring the Royal Academy of Painting and Sculpture, and attending performances at the Comédie Française, their likenesses went everywhere else, as collectible printed portraits (Color Plate 8). News of the ambassadors' activities in France spilled over into special issue after special issue of the society monthly the Mercure Galant. The market was also quickly flooded with published accounts by the French missionaries and diplomats who had spent time in Siam in the 1680s. Through these images and travel narratives, we can study how Siam was viewed, interpreted, and packaged for a mass audience in Europe. But what about the other side of this encounter? All that remains of Kosa Pan's diary, which records a Siamese view of France, is a brief fragment, taken down in a borrowed notebook while he awaited a new supply of paper. The missing diary is a poignant emblem of an even vaster archival gap. A series of disasters and historical calamities, ranging from palace fires to the near-total destruction of the Siamese capital by Burmese forces in 1767, has left in its wake almost no documentary and little material evidence from late seventeenthcentury Siam. Even Thai scholars have relied on European sources in reconstructing not only the seventeenth-century encounter with Europeans but the history of the Siamese court in general.2 This chapter proposes one way that we may fruitfully reconstruct the Siamese interest in Europe through these European sources, and this is by focusing on the practice of collecting. My project is to examine a moment in intellectual history, in both Europe and Siam, that was affected by and reflected in the exchange of objects, and with them, the exchange in points of view. Phra Narai, king of Siam from 1656 to 1688, was an avid collector of the Western and Asian goods traded by the Dutch East India Company and his other diplomatic contacts in Europe. Many of these were luxury items- Chinese ceramics and silks, Persian and Indian textiles, European hats. But Narai and his father, King Prasatthong (1629-56), apparently alone among seventeenth-century Siamese monarchs, had a special interest inWestern optical instruments and scientific apparatuses.3 These were not merely finely crafted and precious trade goods but were closely attached to European intellectual innovations; they were devices that transformed human vision and perception. What evidence there is suggests that Narai actively imported Western modes of seeing along with the instruments that amplified naked vision. Admittedly the Siamese reception of European optical devices and mechanical gadgets is much more difficult to study than is the case for East Asia. In Edo Japan, printed images demonstrate the fashion for acquiring European scientific devices, even when direct contact with the West was forbidden. Siam had no mass media either to diffuse interest in European curiosities within and beyond the court or to serve us now as a record of such interest. In the case of China, actual objects collected from Europe as prestigious curiosities, such as mechanical clocks, still exist, as do Chinese clocks that incorporated European-style mechanisms. 4 While Narai's acquisitions were destroyed or dispersed long ago, the kind of items that appealed to him are listed in the Dutch East India Company records, French Foreign Missions (Missions É trangères) correspondence, and published narratives by European travelers. Among the objects Narai requested or received as diplomatic gifts were telescopes, spyglasses, clocks, spectacles, mirrors, orreries, and terrestrial and celestial globes.5 He even acquired natural specimens, among them stuffed birds, that the Dutch East India Company was shipping back from Indonesia to stock the curiosity cabinets of Europe. Curiosity cabinets brought together man-made artifacts with botanical and zoological oddities. Compared and catalogued in the artificial context of the cabinet, these objects gave rise to new ways of understanding the human and natural worlds. Collecting in seventeenth-century Europe, then, went beyond the pursuit of material objects and was an intellectual and social project. The objects most prized by collectors in the sixteenth and seventeenth centuries had been valued for their rarity; the rules of nature were studied by its exceptions. Curiosity cabinets were the province of "wonder": As a noun, that category of objects that are unusual, novel, or monstrous, but also, as a verb, a ritualized reaction on the part of the viewer. The category of "wonder" or the "marvelous" was central to the Western encyclopedic project of cataloguing the natural and man-made artifacts that global exploration brought back to Europe. By the end of the seventeenth century, however, a less sensational mode of cultural and natural description was coming into vogue. In the very years of Narai's reign, the first natural history of the Indies was being composed by a Dutch East India company bureaucrat, Georg Eberhard Rumpf, who published under the Latinized name Rumphius. He set himself the systematic task of cataloguing the normal range of natural life around him, in all its bizarre forms.6 No such European naturalist devoted years to studying, or sketching, in Siam, but the accounts of those who passed through in the 1680s also participate in this new attitude. From the point of view of King Narai and his court, it was European objects that were rarities. In part, Narai was turning the tables on the Europeans, who became the exotics in his realm, but by acquiring curious and rare objects from Europe, he was also buying into Western systems of value, scientific study, and diplomacy. In Narai's vanished collections of European wonders are clues to the European vantage points that the Siamese monarch had an interest in acquiring or mastering and those that might have been urged on him by his European contacts. Copyright © 2011 University of Pennsylvania Press. All rights reserved.